Planificación Tributaria Internacional: Análisis de los Servicios Intragrupo considerados como gastos de una empresa domiciliada en el Ecuador. Caso Sector Industrial correspondiente al período fiscal 2013 - Aguirre Grey, Tanya Mariuxi (2016)
The present study analyzes the problem that multinational companies in Ecuador, currently have in the industrial sector, when they operate and keep daily transactions with their related companies abroad, considering that sometimes these transactions could represent a risk for tax administrations. Specifically, the kind of service these companies provide to each other is technical assistance, which represents a significant value in the accounts of the company and is one of the intra-group services considered as an administrative and management activity, according to the Organization for Economic Co-operation and Development (OECD), which is an organization that promotes international standards on transfers pricing. In addition, the technical assistance as an administrative and management operation is considered as a deductible expense according to the Ecuadorian tax law. Therefore, the analysis on this thesis focuses on each of the services involved on intra-group transactions (related companies), according to the terms of the contract between the participants, in order to get some evidence that allow the Tax Administration to define if the operations could be imputable to the taxable results of the year (income tax), or if not, to define what kind of operations are such transactions. One of the other issues included as a part of the present analysis is the activities of the shareholders, which are closely linked to the transactions among the head company and its subsidiaries and affiliates, and could become a method of international tax planning thus affecting tax collection of smaller countries as the case of Ecuador. As an example, it was necessary to perform the analysis of a subsidiary company located in Ecuador in 2013. Through the analysis, it was possible to conclude that the services provided by its related (the parent company), really correspond to the guidelines and processes which must be accomplished by all the subsidiaries around the word in order to keep the same standards, it means that this kind of services are in fact, activities related with the shareholders, and therefore, the company in Ecuador should not consider those expenses as a deduction, because they belong to its parent company. In order to perform this analysis, it was necessary the use of applicable tax framework (tax regulations for the period 2013), as well as the OECD guidelines and other documents related with tax matters.